Exploring Trends, Opportunities, and Challenges in the Waqf and Halal Tourism Industry in Malaysia - Aziz, Roslizawati Binti Che; Zainuddin, Siti Afiqah; Rahman, Mohd Safian Abdul; Usolludin, Hazi Hafizah; Musa, Norizan; Mansur, Akhmad; Joha, Muhammad Noh Muhammad (Springer Science and Business Media Deutschland GmbH, 2025)
Waqf and halal tourism are essential sectors within the global tourism industry and are gaining momentum today. This is prompted by the increasing number of Muslim tourists who require travel destinations that accommodate their religious and cultural requirements. Besides having a rich Islamic cultural heritage, Kelantan has the potential to incorporate Waqf into its framework for Halal tourism as well. Historically, when applied to religious, educational, and social welfare projects, Waqf can be mobilized to develop halal tourism infrastructure and preserve Islamic cultural sites and community-based tourism projects to provide a sustainable financing mechanism that conforms with Islamic principles. This article centres on Kelantan, Malaysia, and examines the current trends, opportunities, and challenges in Waqf and halal tourism. This is supported by research that shows the Waqf and halal sectors have to innovate and adopt new technologies. Another describes how cultural and historical elements can shape the setting of halal tourism so that it can meet trends set at a global level. It also made Malaysia one of the best destinations for Muslim tourists by reviewing government programs, setting standards for halal certification, and bringing in a wide range of tourism goods. Thus, the study is located in Malaysia. Subsequently, Kelantan’s rich multi-cultural and religious environment, various local initiatives, and favorable location regarding the potential expansion of substantial Halal tourism are examined in this investigation. This research aims to provide a more in-depth understanding and recommendations for developing Halal tourism in Kelantan to the local governments, business players, and legislators. The result of this project would add to more generalized growth for Malaysia’s tourism industry.